2019
DOI: 10.2147/dmso.s186758
|View full text |Cite
|
Sign up to set email alerts
|

<p>The role of concordant and discordant comorbidities on performance of self-care behaviors in adults with type 2 diabetes: a systematic review</p>

Abstract: Background: Most patients with Type 2 diabetes (T2D) have high number of comorbid chronic conditions that can affect their self-care abilities. Guidelines for diabetes self-care behaviors are disease specific with little attention given to managing T2D with other comorbidities. Identifying comorbidities that either improve or potentially diminish the individual’s capacity to perform effective self-care behaviors is essential to enhance clinical outcomes. One such framework conceptualizes comorbiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 81 publications
0
38
1
Order By: Relevance
“…The prevalence of depression was close to 30% in this study cohort, similar to that reported elsewhere for populations with T2D ( 29 31 ). Depression has been shown to have a negative impact on diabetes self-care behaviors in general ( 32 34 ), although not all analyses have found this ( 29 ). In our study, neither the prevalence of depression nor other psychiatric disease were different between the A1C attainment cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of depression was close to 30% in this study cohort, similar to that reported elsewhere for populations with T2D ( 29 31 ). Depression has been shown to have a negative impact on diabetes self-care behaviors in general ( 32 34 ), although not all analyses have found this ( 29 ). In our study, neither the prevalence of depression nor other psychiatric disease were different between the A1C attainment cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…9 Thus, hypertension, obesity, hyperlipidemia, Chronic Vascular Disease (CVD), and Chronic Kidney Disease (CKD) are commonly reported comorbidities among diabetic patients. [10][11][12][13][14] Furthermore, the studies identified that most adults with diabetes have at least one comorbidity and as many as 40% of them have at least three comorbidities. 15 According to the study conducted among more than 1.3 million participants, more than 97.5% of patients had at least one comorbid condition.…”
Section: Introductionmentioning
confidence: 99%
“…They developed a framework in which chronic conditions are conceptualized as concordant (pathophysiologic profile or management plan similar to T2DM) or discordant (pathophysiologic condition and disease-management plan not directly related to T2DM). With the increasing burden of T2DM comorbidity, the aforementioned framework has served as a basis to improve T2DM management and to study the impact of multimorbidity ( Calderón-Larrañaga et al, 2014 ; Lin et al, 2018 ; Aga et al, 2019 ). Indeed, a recent study in Spain demonstrated that the coexistence of mental and other discordant comorbidities in T2DM patients may increase the use of healthcare resources significantly ( Calderón-Larrañaga et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%